Lipid Modulation of Membrane Protein Function. Issue 7 (19th July 2018) - Whitelegge, Julian
Abstract : In the last decade, native mass spectrometry has emerged as a powerful tool for studying the interactions of lipids and other small molecules with integral membrane proteins and their complexes. In this issue of Cell Chemical Biology, Pyle et al. (2018) establishes the role of phosphatidyl-inositol in dimerization and activity of a eukaryotic purine transporter (UapA). Abstract : In the last decade, native mass spectrometry has emerged as a powerful tool for studying the interactions of lipids and other small molecules with integral membrane proteins and their complexes. In this issue of Cell Chemical Biology, Pyle et al. (2018) establishes the role of phosphatidyl-inositol in dimerization and activity of a eukaryotic purine transporter (UapA).